Konten Instagram @Sushigo_id - Inayah, Ika Risanatul (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2024)
The contribution of Instagram content Sushi Go and similar companies in designing and developing digital marketing content creativity must be effective and expected to help companies to adapt to changing trends and customer preferences that drive innovation in the world of marketing communicationkontribusi konten Instagram Sushi Go dan perusahaan sejenis dalam merancang dan mengembangkan kreativitas konten pemasaran digital harus efektif serta diharapkan membantu perusahaan untuk beradaptasi dengan perubahan tren dan preferensi pelanggan yang mendorong inovasi dalam dunia komunikasi pemasaran